TECHNO-ECONOMIC ANALYSIS OF THE RECONSTRUCTION OF CENTRAL HEATING SYSTEM IN THERMAL POWER PLANT BITOLA - Mijakovski, Vladimir (Termotehnika, 2017)
With the latest modernization and revitalization of blocks in Thermal Power Plant (TPP) Bitola (2010-2012), apart from increasing the power of each unit from 225 to 234,3 MWel, new regulating valves were installed in the section between Medium Pressure Turbine (MPH) and Low Pressure Turbine (LPT) enabling subtraction of steam for the purposes of district heating of Bitola. This also creates opportunity to connect power plant’s own central heating system, with installed heat capacity of approximately 26 MWh, to this heat source. This heating system is in operation for almost 35 years and the need for its revitalization and reconstruction, techno-economic analysis, investment costs, economic viability and return on investment period for the reconstruction are presented in this paper.